2017
DOI: 10.13040/ijpsr.0975-8232.8(9).3696-08
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Chenopodium album (sub sp. striatum) is a folk and nutritious medicine belongs to Chenopodiaceae family and widely used as antimicrobial agent. The aim of this study is to evaluate the in vitro antibacterial potential against multidrug-resistance (MDR) bacteria isolated from clinical spicemens, antioxidant activity, total phenolic and total flavonoids content of crude ethanolic extract and nine different fractions of C. album (sub sp. striatum). The in vitro antibacterial activity was evaluate against eight mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In biological systems, the compounds that eliminate or destroy reactive oxygen species not only exist in human metabolism, but also in plants and fruits. Chenopodium album has antimicrobial activity against different pathogenic bacteria such as P. multocida, K. pneumoniae, Bacillus cereus, S. aureus, P. aeruginosa, B. subtilis, E. coli, and Y. enterocolitica (Adedapo et al, 2011;Khomarlou et al, 2017;Külcü et al, 2019;Parkash & Patel, 2014). Korcan examined the antibacterial activity of methanolic extract and found that it was most effective against B. subtilis (13 mm zone of inhibition at 100 g mL −1 ), and that the activity increased with increasing the extract concentration (Korcan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In biological systems, the compounds that eliminate or destroy reactive oxygen species not only exist in human metabolism, but also in plants and fruits. Chenopodium album has antimicrobial activity against different pathogenic bacteria such as P. multocida, K. pneumoniae, Bacillus cereus, S. aureus, P. aeruginosa, B. subtilis, E. coli, and Y. enterocolitica (Adedapo et al, 2011;Khomarlou et al, 2017;Külcü et al, 2019;Parkash & Patel, 2014). Korcan examined the antibacterial activity of methanolic extract and found that it was most effective against B. subtilis (13 mm zone of inhibition at 100 g mL −1 ), and that the activity increased with increasing the extract concentration (Korcan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ampicillin (20 μg/well) was administered as a control. In vitro, antimicrobial activity was tested by determining the minimum inhibitory concentration (MIC) and minimum lethal concentration (MLC) using micro‐dilution method (Khomarlou et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%